Endothelial nitric oxide synthase, angiotensin-converting enzyme and angiotensinogen gene polymorphisms in hypertensive disorders of pregnancy - Aggarwal, Pardeep Kumar; Jain, Vanita; Jha, Vivekanand (Hypertension research, 2010)
We investigated the variations in genes encoding endothelial nitric oxide synthase ( NOS3 ), angiotensin-converting enzyme ( ACE ) and angiotensinogen ( AGT ) in hypertensive disorders of pregnancy and the relationship between the polymorphisms and circulating nitric oxide (NO) and ACE levels in pregnant north Indian women. Frequencies of NOS3 G894T, 4b/a and T –786 → C, AGT T704C and ACE ins/del polymorphisms were studied in 342 subjects: 120 with preeclampsia (PE), 104 with gestational hypertension and 118 normotensive pregnant women. Variations were evaluated by polymerase chain reaction–restriction fragment length polymorphism. NO and ACE levels were determined using ELISA. There was no difference in the distribution of individual NOS3 and ACE polymorphisms in the study groups. Haplotype analysis showed a global difference in the NOS3 haplotype distribution between the PE and non-PE subjects ( P =0.03). The presence of AGT 704C allele was associated with a reduced risk of developing PE (odds ratio: 0.33, 95% CI: 0.19–0.59 in recessive mode). Circulating total NO and ACE levels were similar in three groups. No relationship was found between circulating NO levels and any of the NOS3 polymorphisms, but the circulating ACE levels were higher in those with DD genotype ( P <0.05). In conclusion, there was no association between individual NOS3 and the ACE gene polymorphisms and hypertensive disorders of pregnancy in north Indian women. The presence of minor alleles at all the three sites in NOS3 seemed to increase the risk of PE, and AGT 704C allele was associated with a reduced PE risk. The complexity of interaction between these genetic abnormalities requires further studies.